Decision Analysis, SAW, Pandemic Analisis Keputusan Perkuliahan Mahasiswa Pasca Pandemi : Analisis Keputusan Perkuliahan Mahasiswa Pasca Pandemi - Endang, Hutami; Malik, Anhar Januar; Yahya, Andi Fauziah (Jurnal INSYPRO (Information System and Processing), 2023)
During the pandemic, all activities require people to work from home and reduce interactions outside in home. This situation lasted a year. The filed of education, Indonesia does not carry out lectures offline or face to face. Many students feel bored in online lectures. It is not uncommon for students complain about the many assignments from the lecture. Pandemic period is recovering. Not many universities in Indonesia hold lecture offline. There are many consideration for students and even parents to support offline lecture. The sense of anxiety that exists in the minds of students to carry out offline lectures. Based on the results of the ranking 50 respondents who werw carried out randomly, was obtained from the highest vectoe value which became altenative choice of conclusions. The results show that A5 has the highest ranking vector to others. Totally 1.71 students don’t agree to do online lecture after pandemic.